Retrieving System Performance - S.Girija, Mrs.; S.Kayathri, Mrs.; S.Meena, Ms. (International Journal of Engineering and Technology, 2018)
A system used for backing files, storing and retrieving. The temporary storage is created for storing the files using hard disk. The operating system makes the backup of all the details. The operating system will be compared and if it same the data and information will be combined. Otherwise distracted information is stored in common file and retrieved.Â
Keywords: Use about five key words or phrases in alphabetical order; Separated by Semicolon